Pengaruh Personal Selling Dan Harga Jual Terhadap Peningkatan Volume Penjualan PT Solid Andalas Makmur Medan - Irina Yoshinta (Jurnal Manajemen Akuntansi Dan Administrasi Bisnis, 2017)
This study aims to determine the effect of personal selling and the selling price to the increased sales volume PT Solid Andalas Makmur Medan. Data were collected based on random sampling of 66 respondents. Data collection method used in this research is to use a questionnaire. Model analysis of the data used is multiple linear regression analysis. Sampling using random sampling method is randomly chosen sample. This data was obtained directly using a questionnaire on customer PT Solid Andalas Makmur Medan. Hypothesis testing tools used in this research is by using SPSS Version 20. Results of research on PT Solid Andalas Makmur Medan indicates that personal selling variables have a significant impact on sales volumes PT Solid Andalas Makmur Medan. Test results on the selling price koefisien multiple linear regression has a positive effect on sales volume but not significantly. Partial results of significance test (t test) showed that personal selling positive and significant impact on sales volume on PT Solid Andalas Makmur Medan.